2021
DOI: 10.4239/wjd.v12.i8.1146
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota as a target for prevention and treatment of type 2 diabetes: Mechanisms and dietary natural products

Abstract: Type 2 diabetes mellitus (T2DM) is among the most remarkable public health concerns globally. Accumulating research evidence documents that alteration of gut microbiota has an indispensable role in the onset and progression of obesity and T2DM. A reduced microbial diversity is linked to insulin resistance and energy metabolism, especially for the rise of the Firmicutes / Bacteroidetes ratio. Changes in metabolites followed by the gut dysbacteriosis are linked to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 134 publications
(149 reference statements)
1
13
0
1
Order By: Relevance
“…16SrRNA third-generation full-length sequencing was used to evaluate the changed characteristics of intestinal microbials of different groups. At the genus level, the abundances of Bacteroides, Prevotella, and Phascolarctobacterium decreased in intestinal flora of the T2DM group, while the abundance of Escherichia increased, which was consistent with previous research (19)(20)(21). In this experiment, the fecal metabolites alpha-linolenic acid, PC(18:3(6Z,9Z,12Z)/24:1(15Z)), and traumatin were enriched in the alpha-linolenic acid metabolic pathway, and alpha-linolenic acid and erucic acid were enriched in the biosynthesis of unsaturated fatty acids, in which the former had a significant positive relationship with Phascolarctobacterium.…”
Section: Discussionsupporting
confidence: 92%
“…16SrRNA third-generation full-length sequencing was used to evaluate the changed characteristics of intestinal microbials of different groups. At the genus level, the abundances of Bacteroides, Prevotella, and Phascolarctobacterium decreased in intestinal flora of the T2DM group, while the abundance of Escherichia increased, which was consistent with previous research (19)(20)(21). In this experiment, the fecal metabolites alpha-linolenic acid, PC(18:3(6Z,9Z,12Z)/24:1(15Z)), and traumatin were enriched in the alpha-linolenic acid metabolic pathway, and alpha-linolenic acid and erucic acid were enriched in the biosynthesis of unsaturated fatty acids, in which the former had a significant positive relationship with Phascolarctobacterium.…”
Section: Discussionsupporting
confidence: 92%
“…The ratio between these phyla is associated with several diseases; it is significantly increased in several models, including T2DM, nonalcoholic fatty liver, and depression. [40][41][42] Several data have shown that diabetes mellitus and obesity can increase the F/B ratio in humans and animals. 43 Lowering the F/B ratio can alleviate metabolic disorders and inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The findings involving the association between gut dysbiosis and DM reinforce the importance of gut-targeting approaches in the treatment of DM[ 19 - 21 ] Strategies capable of recovering the community of commensal GM and controlling DM have recently increased. Probiotic therapy has begun to be used to improve GM composition and management of DM[ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 89%